L’événement fortuit à travers le prisme du nom général - Adler, Silvia (Neophilologica, 2014)
This study undertakes to examine, following Adler (2012) and on the basis of media examples drawn from Le Monde, referential mechanisms involving general nouns such as tragedy, catastrophe, disaster. These nouns refer to events in previous or subsequent chunks of text while delivering the addresser’s opinion in relation to the encapsulated event. Our goal consists in assessing the role of these lexical labels in the representation and interpretation of the event under consideration as well as in identifying the role of the general label in the construction or the mise-en-scène of a media event.